Shuttle Transfer of mRNA Transcripts via Extracellular Vesicles From Male Reproductive Tract Cells to the Cumulus–Oocyte Complex in Rabbits (Oryctolagus cuniculus) - Abumaghaid, Mosleh M.; Abdelazim, Aaser M.; Belali, Tareg M.; Alhujaily, Muhanad; Saadeldin, Islam M. (Frontiers in Veterinary Science, 2022)
Semen is known to contain an ovulation-inducing factor (identified as a nerve growth factor, NGF) that shows a significant increase in ovulation after semen deposition in induced-ovulatory species. However, the interplay between the male reproductive tract cells and the oocyte maturation through mRNA cargo yet to be investigated. Extracellular vesicles (EVs) from the primary culture of rabbit prostate (pEVs), epididymis (eEVs), and testis (tEVs) were isolated to examine their contents for several mRNA transcripts through RT-qPCR. Expression of NGF, neurotrophin (NTF3), vascular endothelial growth factor (VEGFA), A disintegrin and metalloprotease 17 (ADAM17), midkine (MDK), kisspeptin (KISS1), and gonadotrophin-releasing hormone (GNRH1), were examined in the isolated EVs. EVs were characterized through transmission electron microscopy. EV uptake by cumulus cell culture was confirmed through microscopic detection of PKH26-stained EVs. Furthermore, the effects of pEVs, eEVs, and tEVs were compared with NGF (10, 20, and 30 µM) supplementation on oocyte IVM and transcript expression. KISS1, NTF3, MDK, ADAM17, GAPDH and ACTB were detected in all EV types. GNRH1 was detected in tEVs. NGF was detected in pEVs, whereas VEGFA was detected in eEVs. pEVs, eEVs, and 20 µM NGF showed the highest grade of cumulus expansion, followed by tEVs and 10 µM NGF. Control groups and 30 µM NGF showed the least grade of cumulus expansion. Similarly, first PB extrusion was significantly increased in oocytes matured with eEVs, pEVs, tEVs, NGF20, NGF10, control, and NGF30. Additionally, ADAM17 expression showed a 1.5-fold increase in cumulus cells supplemented with tEVs compared with the control group, while PTGS2 (COX2) expression showed a 1.6-fold increase in NGF20-supplemented COCs. Oocyte PMP15 expression showed a 1.8-fold increase in IVM medium supplemented with eEVs, while GDF9 showed a 1.6-fold increase in IVM medium supplemented with pEVs. Additionally, oocyte NGFR and NTRK expression were drastically increased in IVM medium supplemented with pEVS (7.8- and 4.6-fold, respectively) and tEVs (2- and 1.7-fold, respectively). This is the first report to examine the presence of mRNA cargo in the EVs of male rabbit reproductive tract cells that provide a model for the stimulation of female rabbits after semen deposition.